Positional Enrichment by Proton Analysis (PEPA): A One‐Dimensional 1H‐NMR Approach for 13C Stable Isotope Tracer Studies in Metabolomics. Issue 13 (21st February 2017) - Vinaixa, Maria; Rodríguez, Miguel A.; Aivio, Suvi; Capellades, Jordi; Gómez, Josep; Canyellas, Nicolau; Stracker, Travis H.; Yanes, Oscar
Abstract: A novel metabolomics approach for NMR‐based stable isotope tracer studies called PEPA is presented, and its performance validated using human cancer cells. PEPA detects the position of carbon label in isotopically enriched metabolites and quantifies fractional enrichment by indirect determination of 13 C‐satellite peaks using 1D‐ 1 H‐NMR spectra. In comparison with 13 C‐NMR, TOCSY and HSQC, PEPA improves sensitivity, accelerates the elucidation of 13 C positions in labeled metabolites and the quantification of the percentage of stable isotope enrichment. Altogether, PEPA provides a novel framework for extending the high‐throughput of 1 H‐NMR metabolic profiling to stable isotope tracing in metabolomics, facilitating and complementing the information derived from 2D‐NMR experiments and expanding the range of isotopically enriched metabolites detected in cellular extracts. Abstract : PEPA is a novel technique for extending the high‐throughput of 1 H‐1D‐NMR metabolic profiling to 13 C stable isotope tracing. The approach broadens the range of isotopically enriched metabolites detected in cellular extracts, thus accelerating the implementation of NMR in cell metabolism studies.